Manajemen Pembelajaran Diferensiasi dalam Meningkatkan Motivasi Belajar Siswa - Kukuh Jaya Barokah; Yanti Apriyanti; Suharyanto H. Soro; Ida Tejawiani (Civiliza Publishing, Indonesia., 2026)
Differentiated learning has not been implemented optimally so that it affects the increase in learning motivation. This study aims to explore differentiated learning in increasing student learning motivation. This study uses a case study approach. Samples or respondents were selected purposively involving school principals and curriculum teachers. Data collection methods used observation, interviews, and documentation studies. The results of the study indicate that (1) Differentiated learning planning has been structured according to school needs; (2) The organization of differentiated learning is carried out by following established norms and procedures, namely the division of tasks and responsibilities; (3) The implementation of differentiated learning is carried out consistently and procedurally according to the plan. Control/Evaluation of differentiated learning starts from the assessment stage to follow-up. The conclusion of this study is that properly managed differentiated learning can increase student learning motivation.